2022
DOI: 10.1186/s12891-022-05361-2
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of intravenous tranexamic acid in patients with posterior operation of multilevel thoracic spine stenosis: a prospective randomized controlled trial

Abstract: Background This study was a randomized controlled trial to evaluate efficacy and safety of the usage of intravenous tranexamic acid during posterior operation of multilevel thoracic spine stenosis for controlling perioperative blood loss. Methods Sixty eight patients with multilevel thoracic spine stenosis were randomized into the tranexamic acid group receiving 15 mg/kg body weight before the skin incision was made and 1 mg/kg body weight per hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…Meanwhile, research supporting TXA efficacy and safety in adult spine surgery has also been increasing [44,45]. Multiple recent studies, including one randomized control trial of 68 thoracic spine stenosis patients and a retrospective analysis of 122 patients undergoing lumbar fusion, did not find any associated side effects with TXA use including the incidence of DVTs [46,47]. Our findings are in line with this growing body of work demonstrating safety of TXA use in spine surgery.…”
Section: Discussionsupporting
confidence: 85%
“…Meanwhile, research supporting TXA efficacy and safety in adult spine surgery has also been increasing [44,45]. Multiple recent studies, including one randomized control trial of 68 thoracic spine stenosis patients and a retrospective analysis of 122 patients undergoing lumbar fusion, did not find any associated side effects with TXA use including the incidence of DVTs [46,47]. Our findings are in line with this growing body of work demonstrating safety of TXA use in spine surgery.…”
Section: Discussionsupporting
confidence: 85%
“…For orthopedic trauma, TXA can reduce hidden blood loss related to intertrochanteric fractures and tibial plateau fractures but does not increase the risk of postoperative venous thromboembolism [ 25 27 ]. In spinal surgery, TXA can significantly reduce the total perioperative blood loss volume without obvious side effects [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…TXA is widely used in lumbar fusion surgery because it reduces IBL, OT, LOS, and even blood transfusion rates. [9–34] A systematic review and meta-analysis by Gong et al demonstrated that intravenous TXA during PLIF surgery is safe and can help reduce surgical blood loss; however, the authors concluded that it does not reduce transfusion rates. [10] Bai et al made similar conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…[11,12] In addition, more than one study has found that intraoperative TXA use can reduce PDV and LOS. [13][14][15][16][17][18] However, no studies have reported whether using TXA or not using TXA within 24 hours after surgery will result in different perioperative clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation